Pengembangan Tugas Autentik Pada Pembelajaran Matematika Model GI-TTW Untuk Meningkatkan Kreativitas Siswa - Zahroh, Alfiatuz; Pradita, Mutiea Ira (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: The purpose of this study was to develop an authentic task based on the GI-TTW (Group Investigation–Think Talk Write) model to enhance students’ creativity. This research employed the Research and Development (R&D) method using the Plomp development model, which consists of three stages: (1) preliminary research, including problem analysis and material analysis; (2) prototyping phase, involving the development of authentic tasks in the form of LKPD (student worksheets), pretest and posttest instruments, validity instruments, and practicality questionnaires; and (3) assessment phase, which includes the validation, practicality, and effectiveness testing of the product. The research subjects were students of class XI-B at SMA Hang Tuah 4 Surabaya. The validation results showed a score of 83% from content experts and 85% from design experts, indicating that the developed product falls into the "very valid" category. Practicality testing resulted in an average score of 75% from teachers and 80% from students, categorized as "practical" and "very practical." Meanwhile, the effectiveness was demonstrated by a classical mastery percentage of 88% and an average n-gain score of 0.82, which is considered “high.” Therefore, the developed product is declared valid, practical, and effective.   ABSTRAK: Tujuan penelitian ini gunamengembangkan tugas autentik berbasis GI-TTW (Group Investigation–Think Talk Write) gunameningkatkan kreativitas subjek penelitian. Penelitian ini dilakukan sesuai dengan model pengembangan Plomp yaitu investigasi awal (pleminary research): analisis masalah serta analisis materi; pembuatan prototipe (prototyping phase): membuat tugas autentik berupa LKPD, tes (pretest serta posttest), instrumen validitas, serta angket kepraktisan;  serta penilaian (assessment phase): uji kevalidan, kepraktisan, serta keefektifan produk. Subjek penelitian adalah kelas XI-B SMA Hang Tuah 4 Surabaya. Hasil uji kevalidan menunjukkan bahwa skor validasi dari ahli materi sebesar 83% serta dari ahli desain sebesar 85%, sehingga tugas autentik yang telah dibuat termasuk kategori “sangat valid”. Uji kepraktisan menunjukkan skor rerata 75% dari guru serta 80% dari subjek penelitian, yang termasuk kategori “praktis” serta “sangat praktis”. Sementara itu, tingkat keefektifan ditunjukkan oleh persentase ketuntasan klasikal sebesar 88% serta rerata indeks n-gain sebesar 0,82, yang termasuk dalam kategori “tinggi”. Dengan demikian, produk yang dikembangkan dinyatakan valid, praktis, serta efektif.